Radical radiation therapy for oligometastatic breast cancer: Results of a prospective phase II trial. Issue 1 (January 2018) - Trovo, Marco; Furlan, Carlo; Polesel, Jerry; Fiorica, Francesco; Arcangeli, Stefano; Giaj-Levra, Niccolò; Alongi, Filippo; Del Conte, Alessandro; Militello, Loredana; Muraro, Elena; Martorelli, Debora; Spazzapan, Simon; et al.
Abstract: Background and purpose: We conducted a prospective phase II multicentric trial to determine if radical radiation therapy to all metastatic sites might improve the progression-free survival (PFS) in oligometastatic breast cancer patients. Secondary endpoints were local control (LC), overall survival (OS) and toxicity. Methods and materials: Inclusion criteria were the following: oligometastatic breast cancer with ≤5 metastatic sites, FDG-PET/CT staging, no brain metastases, primary tumor controlled. Radiotherapy could be delivered using stereotactic body radiotherapy (SBRT) technique or fractionated intensity modulated radiotherapy (IMRT). SBRT consisted of 30–45 Gy in 3 fractions, while IMRT was delivered to a total dose of 60 Gy in 25 fractions. We hypothesized that radical radiation therapy could increase the PFS from 30% (according to the published literature) to 50% at two years. Results: 54 Patients with 92 metastatic lesions were enrolled. Forty-four were treated with SBRT, and 10 with IMRT. Forty-eight (89%) patients received a form of systemic therapy concomitantly to radiation therapy. Sites of metastatic disease were the following: bones 60 lesions, lymph nodes 23 lesions, lung 4 lesions, liver 5 lesions. After a median follow-up of 30 months (range, 6–55 months), 1- and 2-year PFS was 75% and 53%, respectively. Two-year LC and OS were 97% and 95%, respectively. Radiation therapy was well tolerated, and no Grade ≥3 toxicity was documented. Grade 2 toxicity were pain and fatigue in 2 cases. Conclusions: Patients with oligometastatic breast cancer treated with radical radiotherapy to all metastatic sites may achieve long-term progression-free survival, without significant treatment-related toxicity. While waiting for data from randomized trials, the use of radical radiation therapy to all metastatic sites in patients with oligometastatic breast cancer should be considered a valuable option, and its recommendation should be individualized.